A THE EFFECT OF IMPLEMENTING PROBLEM BASED LEARNING WITH VIDEO MEDIA ON CRITICAL THINKING SKILLS, CREATIVE THINKING SKILLS AND UNDERSTANDING STUDENT CONCEPTS - Suseno Suseno; Didimus Tanah Boleng; Susilo Susilo (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2020)
This study aims to determine the effect of the application of problem-based learning with video media on critical thinking skills. The data analysis technique used the Kruskal Wallis statistical test The ability of critical thinking skills, creative thinking skills, and understanding of students' concepts is still low so it needs to be improved to achieve minimal learning completeness. The sampling technique used research instruments and test question sheets. The sample of students in grades VII-A, VII-B, VII-D of SMP Negeri 2 Tenggarong Seberang, Kutai Kartanegara Regency, East Kalimantan Province, Indonesia.. The results of the data analysis showed that the Problem Based Learning model with video media had no significant effect on critical thinking skills with H = 4.17 and students' conceptual understanding with H = 2.588 but had a significant effect on creative thinking skills with H = 12.659 so that it affected learning completeness.